Contributions to determine paleoenvironments, coals syncline ChecuaLenguazaque. Colombia (2016)
This study aims to make new contributions to the knowledge and interpretation of paleoenvironment of Guaduas Formation´s coals, Superior Maestrichtian to Paleocene age. Petrographic analysis of 64 samples collected them by the channel method in three sections of the Checua-Lenguazaque syncline (Sutatausa, Guachetá and Samacá), establishing that the coals are composed mainly of macerals of the vitrinite group with percentages between (51.4% - 87%), followed by the inertinite group (5.4% - 43.8%), liptinite (0.2% - 14%), and mineral matter (0.4% - 18%). The average vitrinite reflectance ranged from 0.69 to 1.6; showing bituminous coals C to bituminous coals A. The maceral reading allowed the determination of the distribution of organic components of coal to implement the methodology proposed by Diessel (1992) and the used it by Singh & Singh (2000), for the definition of palaeoenvironments; concluding that the coals of Guachetá and Samacá blocks were deposited in environments of protected areas for barriers and bogs mainly, while the coals of the Sutatausa block extended into wet-forest swamps. Table water although variable, covered the peat bog which favored the preservation of organic material against oxidation.